2021
DOI: 10.21037/atm-21-445
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features in coronavirus disease 2019 (COVID-19) patients with early clearance and prolonged shedding of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA

Abstract: Background: Since the outbreak of coronavirus disease 2019 , the pattern of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA shedding has not been well characterized.Methods: In our study, 652 patients in Wuhan Designated Hospital were recruited, and their clinical and laboratory findings were extracted and analyzed. Results:The median duration of SARS-CoV-2 RNA detection was 23 days [interquartile range (IQR), 18 days] from symptom onset. Compared to patients with early viral RNA clearance (<2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
12
2
1
Order By: Relevance
“…These findings are in accordance with some previous analyses demonstrating that the viral load increases with age [ 21 ] and is higher in females [ 22 ]. However, we also cannot use underlying comorbidities, such as arterial hypertension and diabetes, as moderator variables, which have been related to a slower viral shedding [ 23 , 24 ]. Moreover, the intrinsic and unmodifiable heterogeneities existing among laboratories have also doubtlessly influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with some previous analyses demonstrating that the viral load increases with age [ 21 ] and is higher in females [ 22 ]. However, we also cannot use underlying comorbidities, such as arterial hypertension and diabetes, as moderator variables, which have been related to a slower viral shedding [ 23 , 24 ]. Moreover, the intrinsic and unmodifiable heterogeneities existing among laboratories have also doubtlessly influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Several other studies have also revealed the presence of fever was significantly associated with prolonged DoVC ( Zhou et al, 2021 ; Bennasrallah et al, 2021 ). These patients were hypothesized to be more severely affected by the SARS-CoV-2 infection in the lungs and thus the prolonged DoVC ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 72%
“…Several other studies have also revealed the presence of fever was significantly associated with prolonged DoVC ( Zhou et al, 2021 ; Bennasrallah et al, 2021 ). These patients were hypothesized to be more severely affected by the SARS-CoV-2 infection in the lungs and thus the prolonged DoVC ( Zhou et al, 2021 ). Fever at illness onset may indicate a cytokine storm or a higher viral load at the time of symptom onset ( Chau et al, 2021 ), as the viral load was found to be associated with more severe COVID-19 and a longer virus-shedding period ( Liu et al, 2020b ).…”
Section: Discussionmentioning
confidence: 72%
“…Manzulli et al demonstrated that patients showed the viral clearance at viral culture three days or more after clinical recovery [36]. However, other studies reported the persistence of active infection and contagiousness in immunocompromised or severely ill patients [9,[11][12][13][14][37][38][39]. In line with these studies, long term shedding of viable virus was infrequent in our study (10 out of 138 cultured samples, 7.2%) and was nearly limited to patients with conditions associated with prolonged RT-PCR positivity and/or severe COVID-19, but the risk of transmission was still present after three weeks from diagnosis.…”
Section: Discussionmentioning
confidence: 99%